Percepção da comunidade Pimenteira com relação às ações conservacionistas da RPPN SESC Pantanal-Barão de Melgaço-MT - Pimentel, Cristina Cuiabália Rodrigues (Pontificia Universidad Católica del Perú. Centro de Investigación en Geografía Aplicada, 2013)
This paper has as its goal to study the perception of the dwellers from Pimenteira community in relation to the conservative actions of the Private Reservation of the Natural Patrimony (PRNP) SESC Pantanal – Barão de Melgaço-MT. It is characterized as a research mostly qualitative done in two stages. The first, conducted through field research guide-book containing the main aspects of the community, and the second stage was done through semi-structured interviews for the obtainment of data on the perception of the community. The results revealed that the under-structure is poor which compromises the basic needs of the population. On the second stage of the work, it was diagnosed that the PRNP is a positive thing to the community because it brought jobs and income and the environmental conservation was left in a third plan. Most of the population do not know actions of handling and its importance to the environment. The few people who mentioned some actions pulled out the fight against the forest fires as a job opportunity. These results point to a reformation of the techniques of handling, searching for participative techniques to achieve integrated maintenance among all dimensions.